Women and Leadership (Springer International Publishing, 2018)
This empowering volume presents current empirical findings and rich personal insights into the evolving challenges women face in attaining-and thriving in-leadership positions. Contributors add new voices to emerging and familiar topics, including leadership styles and traits, growth and learning experiences within career paths, mentoring and entrepreneurial aspects of leadership, and workplace and societal resistance to women in roles of power. Representative first-person accounts shed significant light on real-world double standards and double binds (including the unique obstacles faced by minority women), why the glass ceiling still exists, and steps still needed to dismantle it. Coverage also addresses related legal issues, such as the ongoing fight against pay inequities and conflicts between the DeVos rules and Title IX regulations in the schools. Included among the topics: · · Turn ah-ha moments into pivotal learning. · The important role of women in social entrepreneurship. · Focus group becomes support group: women in educational leadership. · Issues confronting women leaders in academia: the quest for equality. · Leadership means using the courts to demand equal enforcement of and protection for women's constitutional and civil rights. · Organizations concerned with women and leadership. Whether one's interest is local or global, scholars and students in courses on leadership, career development, and women's studies will find Women and Leadership inspiring and stimulating in myriad domains, from research and business to politics and policy.